Counting crime: Discounting victims?. Issue 1 (January 2022) - Hall, Matthew
This paper sets out to critically explore the connections drawn by Her Majesty's Inspectorate of Constabulary and Fire & Rescue Services between police adherence to national crime recording standards and the provision of service and support by the police to victims of crime. The goal of the paper is to identify what assumptions are being made by Her Majesty's Inspectorate of Constabulary and Fire & Rescue Services concerning how and why 'accurate' crime recording impacts upon victims and to test those assumptions against the broader victimological literature. In so doing, the paper will also shed light on the progress made by police services in this regard since significant concerns were raised about the impact of 'poor' crime recording on victims of crime by Her Majesty's Inspectorate of Constabulary in its 2014 report Crime-recording: Making the victim count .